Resposta :
Resposta:
Explicação passo a passo:
[tex]f(2)=8[/tex]
[tex]f(p+1)=f(p)+f(1)[/tex]
[tex]Vamos\;trocar\;"p"\:por\:1\:ok![/tex]
[tex]f(1+1)=f(1)+f(1)[/tex]
[tex]f(2)=2.f(1)[/tex]
[tex]8=2.f(1)[/tex]
[tex]f(1)=8/2[/tex]
[tex]f(1)=4[/tex]
[tex]Vamos\;trocar\;"p"\:por\:2\:ok![/tex]
[tex]f(2+1)=f(2)+f(1)[/tex]
[tex]f(3)=f(2)+f(1)[/tex]
[tex]f(3)=8+4[/tex]
[tex]f(3)=12[/tex]
[tex]Vamos\;trocar\;"p"\:por\:3\:ok![/tex]
[tex]f(3+1)=f(3)+f(1)[/tex]
[tex]f(4)=f(3)+f(1)[/tex]
[tex]f(4)=12+4[/tex]
[tex]f(4)=16[/tex]
[tex]Resposta:(c)[/tex]